2011
DOI: 10.1038/hr.2010.266
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-related adjunctive systo–diastolic ventricular dysfunction in patients with hypertension: echocardiographic assessment with tissue Doppler velocity and strain imaging

Abstract: Very few data exist regarding the effect of obesity on both left and right systo-diastolic ventricular function in hypertensive patients. Therefore, the aim of this study was to determine the existence and extent of an obesity-related adjunctive depressive effect on left-and right-ventricular systo-diastolic dysfunction. This study compared non-obese with obese hypertensive patients and evaluated left-and right-ventricular morphological and functional parameters by means of conventional echocardiography and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Regardless of age and severity of obesity, data on the effect of obesity on myocardial mechanics are scarce. Previous studies using color TDI have demonstrated reduced myocardial velocities, strain, and SR in obese adults (9,10,11,12,13) and children and adolescents (5,14). As a result of TDI angle‐dependency, obesity‐related myocardial deformation alterations reported in these studies were principally restricted to basal segments evaluated in apical views.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Regardless of age and severity of obesity, data on the effect of obesity on myocardial mechanics are scarce. Previous studies using color TDI have demonstrated reduced myocardial velocities, strain, and SR in obese adults (9,10,11,12,13) and children and adolescents (5,14). As a result of TDI angle‐dependency, obesity‐related myocardial deformation alterations reported in these studies were principally restricted to basal segments evaluated in apical views.…”
Section: Discussionmentioning
confidence: 90%
“…Reduced longitudinal strains as well as systolic and diastolic strain rates (SR) measured using color tissue Doppler imaging (TDI) have been found in adults (9,10,11,12,13) and recently in children and adolescents (5,14) with obesity. The angle‐dependency is a serious limitation of all Doppler‐based techniques (15) and most of the aforementioned studies reported data only on myocardial longitudinal function.…”
Section: Introductionmentioning
confidence: 99%
“…DD has clinical, prognostic and therapeutic ramifications. 23, 24, 25, 26, 27 Hypertension, LV hypertrophy, diabetes mellitus and insulin resistance are complications of obesity and have all been associated with worsening of DD. 10 In fact, these cardiovascular risk factors were much more prevalent in the obese and morbidly obese patients than those with normal BMI for all patients and those <35 years old (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies for detecting LV systolic functions in EHT patients depend mainly on tissue Doppler imaging (TDI), cardiac magnetic resonance imaging (cardiac MRI), and cardiac radionuclide imaging. [2][3][4] However, these techniques all have limitations, like angle dependence in TDI, 5,6 long-term examination in cardiac MRI, and radioactivity of cardiac radionuclide imaging. Two-dimensional speckle-tracking echocardiography (2D-STE) has become one of the leading reliable diagnostic techniques for the assessment of cardiac functions because of its non-invasiveness, convenience, and repeatability.…”
Section: Introductionmentioning
confidence: 99%